The significance of RB1 in multiple myeloma - Wang, Yiwen; Yang, Rui; Liu, Rui; Yang, Ruoyu; Lin, Zujie; He, Aili (Frontiers in Immunology, 2024)
The treatment of multiple myeloma (MM) has significantly advanced; however, the underlying genetic mechanisms remain elusive. Clonal events and genetic alterations are recognized as pivotal in the pathogenesis of MM. It is now understood that a multitude of gene mutations, including those affecting RAS, TP53, RB1, and 1q21 amplification, are prevalent in this disease. The incorporation of several high-risk genetic factors into the Second Revision of the International Staging System (R2-ISS) underscores the prognostic significance of genetic aberrations in MM. The retinoblastoma gene (RB1), located in 13q14, encodes the retinoblastoma protein (pRB), a tumor suppressor that regulates cell cycle progression. Deletion of RB1, which is a frequent event in MM, contributes to tumorigenesis by disrupting cell cycle control. In this respect, RB1 loss has been implicated in the progression of MM through its influence on interleukin-6 (IL-6) secretion and cell proliferation. This review comprehensively summarizes the role of RB1 in MM and expounds on the potential of targeting RB1 as a therapeutic strategy for this malignancy.